Psychosocial risks and mental health of health and social care workers in the context of the COVID-19 pandemic - Nadia Vilahur Chiaraviglio (Archivos de Prevención de Riesgos Laborales)
Certainly, our perception of the world we live in has changed since COVID-19 irrupted in our lives in March 2020. Many of our certainties in the European continent were shaked by the unequivocal evidence of our vulnerability as individuals and our lack of preparedness as a society to manage a health emergency of unknown boundaries, despite having one of the most well-developed health systems across the globe.